Hakikat Ilmu dan Transformasi Pengetahuan: Kritik Filsafat Ilmu dalam Konteks Masyarakat Digital - Asep Saiful Alfazr; Ai Patimah Sahra; Jenuri Jenuri (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The main issue in this study is how the nature of science is understood in classical philosophy of science and how the transformation of digital knowledge poses new challenges to the epistemology, ontology, and axiology of science. The purpose of this study is to analyze the nature of science from the perspective of philosophy of science, examine the transformation of knowledge in the digital age, and formulate conceptual critiques to maintain the integrity of science. The research uses a qualitative approach with a library research method that focuses on classic books on the philosophy of science as well as national and international scientific articles on big data, artificial intelligence, virtual reality, and digital ethics. The results of the study show that the nature of science is dynamic: ontology extends to virtual reality, epistemology shifts towards data sources and algorithms with problems of validity and transparency, while axiology demands the integration of ethics and social responsibility in the use of technology. The conclusion of this study emphasizes that the philosophy of science plays an important role as a critical filter amid the crisis of validity, algorithmic bias, and degradation of values. Looking ahead, integrating the philosophy of science into education, strengthening digital literacy, and developing philosophy of science studies based on digital phenomena are strategic steps to maintain the relevance of science in contemporary society.